THE EFFECT OF I-CHAT (I CAN HEAR AND TALK) INSTRUCTIONAL MEDIUM TOWARD HEARING IMPAIRMENT STUDENTâS SPEAKING ABILITY - Meilza W, Norista; Kurniawan, Agung (Department of Special Education, 2016)
Hearing impairment students are unable to communicate verbally due to the stiffness of their speech organs so that their teacher and people around them could not understand their speaking frequently. The spoken word was often unclear so it was misunderstood frequently happened both in the school and house.This study employed Single Subject Research (SSR) with A-B research design After the data processing, mean at 55.2% of the subject âZAâ in baseline phase was obtained. Besides, the mean of intervention phase was 75.5% and the overlap value was 0%. Based on the finding, it could be concluded that the use of I-Chat affects the speaking ability of hearing impaired students of grade VII SMPLB YPTB Malang.